Ushul Fiqh Sebagai Kunci Memahami Syariat Islam - Al Mirza, Ahmad habibie; Sukron Siregar, Abdan; Al Mirza , Ahmad Habibie; Hidayat, Fatmah Taufik (JISH: Jurnal Ilmu Syariah dan Hukum, 2025)
This study aims to examine the role of Ushul Fiqh as the key to comprehensively understanding Islamic Sharia. The primary focus of this research is to demonstrate how Ushul Fiqh provides a systematic methodology that enables Muslims to extract legal rulings from authentic sources and apply them to various aspects of daily life. The study also investigates how Ushul Fiqh bridges the gap between religious texts and the evolving social realities, and how these principles can help resolve contemporary legal issues that are not explicitly addressed in the Qur'an or Hadith. This research adopts a descriptive-analytical approach, reviewing a wide range of classical and modern literature in Ushul Fiqh. It also includes an analysis of how the principles of Ushul Fiqh are applied in addressing contemporary legal issues, such as family law, Islamic economics, and social laws related to the progress of time and technology. The findings of this study suggest that Ushul Fiqh not only provides a means for understanding Islamic law but also functions as a foundational framework for thinking critically and systematically in addressing more complex legal matters. Furthermore, this study emphasizes the role of Ushul Fiqh in assisting Muslims to develop dynamic legal knowledge that is relevant to the changing times and responsive to ongoing social transformations. By understanding Ushul Fiqh, Muslims can apply Islamic law more accurately and maintain its authenticity in a broader context, where the challenges of the modern world continue to unfold